Identificação e caracterização dos mecanismos erosivos atuantes na voçoroca do areal no município de Cacequi/RS com auxílio de veículo aéreo não tripulado - Rademann, Lucas Krein (2019)
The issue of erosion has been widely studied in recent decades, given its great potential for soil and landscape degradation. Among the erosion forms, the gully is the one with the greatest destructive power, making its study and understanding important. Recently the emergence of new technologies such as UAVs has made it possible to made high-quality, detailed low-cost maps, enabling a more complete analysis of the phenomenon. In the municipality of Cacequi, areas with accelerated gulling processes are commonly found, including the Voçoroca do Areal, the object of study of this dissertation. Facing the erosion problematic aspects and the necessity of integrating the geographic science to the new geotechnologies, the main objective of this work is to analyze the distribution and the action of the erosion mechanisms in the Voçoroca do Areal in the municipality of Cacequi with the aid of UAV. For this, aerial survey was performed using UAV and later processed using the Structure from Motion (SfM) technology, generating very high-resolution data that allow the gully morphometric analysis. The Voçoroca do Areal was subdivided into four sectors, which demonstrated to have distinct erosion mechanisms acting and of varying intensities. The mass movements, associated with subsurface erosion provide the main gully development agent, acting on upstream and sidewall gully advancement. In general, the work demonstrates the complexity of the action of erosive mechanisms in a large gully. The innovative methodology used for erosion study open space for further studies of level of detail in accelerated erosion processes.